IMPACT SUSTAINABILITY IN FOOD SUPPLY CHAIN: SCOPING REVIEW (Journal of Technology and Operations Management, 2025)
Food supply chains must balance environmental, economic, and social success to survive. Food supply chains must incorporate strategies that lessen their negative effects on the environment, increase economic resilience, and promote social well-being to be viable over the long run. However, food supply chain faces many quality and efficiency issues. Poor cold chain facilities, transportation and logistics inefficiencies, unsuitable handling equipment, poor road infrastructure, and restricted supply chain partner information sharing are major challenges. These cause significant supply chain losses and waste. Based on a scoping review, this study will investigate impact sustainability in food supply chain and a total of 18 article were analysed. This scoping review of the literature was performed utilising two databases, Web of Science (WoS) and Scopus, to ascertain the characteristics of published scientific literature on this subject and to identify the rising topics of sustainability in food supply chain research. This study identified six primary themes and eighteen sub-themes concerning sustainability within the food supply chain setting. The primary themes encompass organizational readiness, technology, Green Practice, policy, sustainable resourcing, and external relationships. The review suggests that the majority of studies focus on the effects of sustainability within the food supply chain. These results imply that organisations might improve food supply chains, especially during unexpected periods, by considering all impact sustainability. It also provides a comprehensive overview how sustainability can impact efficiency food supply chain. Base on the finding sustainability is gaining popularity, but most study focusses on its effects rather than solutions. Future research must focus on pragmatic, sustainable methods to boost the food supply chain.